Perceived innovation characteristics as predictors of green practice adoption in the Nigerian hotel industry - Mu'azu, Ladi (2017)
Green practice has frequently been acknowledged as an essential and common concept, which businesses implement to achieve some business superiority over competitors.However, studies on environmental practices are seldom conducted in Nigeria.The objective of this paper is to examine the influence of perceived innovation characteristics on the adoption of green practices in the hotel. Samples were collected using proportionate stratified random sampling.Data were collected using 80 questionnaires from the 100 distributed, and then analyzed using statistical package for social sciences (SPSS).Founded on theory of diffusion, this study evaluated three measurements of perceived innovation characteristics influencing the likely adoption of green practices from the perspectives of general managers in the four and five star rated hotels in Kaduna.The study model proposes that hotel's intention to embrace green practices is influenced by the three dimensions of innovation characteristics: perceived compatibility, perceived complexity and the apparent relative advantage.A multiple regression performed indicates perceived compatibility and relative advantage relating positively to likelihood of adoption.The outcomes of this paper may offer valuable understandings of green practices.The findings of this study are practically useful for general managers when developing and implementing organizational innovative policies to ensure sustainable operations.